Hydroxyapatite as bone graft materials to support dental implant treatment: systematic review - Djaswandini, Fairuz Zahira; Hardianto, Andri; Yuza, Abel Tasman (Padjadjaran Journal of Dentistry, 2024)
Introduction: Implant placement after tooth loss can prevent an alveolar bone resorption. Bone grafting is used to obtain adequate quantity and quality of alveolar bone to support dental implants. Hydroxyapatite is the primary synthetic bone graft biomaterial, with a composition and structure similar to natural bone. Hydroxyapatite biomaterials have been widely researched and developed. This study aims to summarize the modified HA materials that have been successfully used in supporting dental implant treatment. Methods: This review was conducted using a systematic review method that refers to systematic literature review simplification with PICO framework, based on PRISMA guidelines. Literature searches were performed through Science Direct, PubMed, Google Scholar, SAGE Journals, and Cochrane Library, for articles published between 2016 – 2021. Inclusion criteria for this review consisted of research articles on the use of hydroxyapatite bone graft in dental implant treatment. Results: Analysis was carried out on 11 articles on the use of hydroxyapatite bone graft in dental implant treatment with various material modifications: sintered, carbonated, eggshell-derived, 3D printed, obtained by sponge replica method, and in combination with rhBMP-2, PRF membrane, collagen membrane, and amniotic membrane. Additionally, hydroxyapatite also comes in several forms: porous block, granular, and nano-sized. Treatment success was observed through histology and histomorphometry analysis; SEM, XRD, FTIR, CBCT, and CT-Scan imaging; and ISQ value. Conclusion: This review demonstrates the modified hydroxyapatite, in combination with other materials or in various form, successfully supports dental implant treatment. This success is attributed to good osseointegration between bone and implant, bone growth, and increase in bone thickness, which are influences by the materials composition and morphology.